The integrated governance model : a case study of HP-Pertubuhan Peladang Kawasan - Sue, Chern Ooi (Penerbit Universiti Kebangsaan Malaysia, 2021)
This study examines the extent of the governance practices in a farmers’ organisation known as HP-Pertubuhan Peladang Kawasan (HP-PPK). Conceptually, the research is framed within the governance framework of the Confederation of Finnish Cooperatives that examines the external, internal, and democratic governance structures of a membership organisation. Data of the study are derived from a series of interviews conducted, observation, and documentation analysis. The study found that HP-PPK has good governance practices, and the board and management manage to develop a mutual understanding of their respective roles. HP-PPK continuously campaigns to attract more farmers to join the PPK, and ultimately, it manages to create strong connections, trust, and relationships with its farmer-members. However, HP-PPK was subject to political interference and relied heavily on the general manager appointed by the Registrar in the management and administration of the PPK. Consequently, there is a severe concern about whether democracy in HP-PPK was undermined and HP-PPK would be transformed into an independent and progressive PPK.